Investigation of pollutant metals in road dust in a post-industrial city: Case study from Detroit, Michigan - Denny, Max; Baskaran, Mark; Burdick, Scott; Tummala, Chandra; Dittrich, Timothy (Frontiers in Environmental Science, 2022)
Inhalation and/or ingestion of toxic heavy metals enriched in road dust have toxic effects on humans. From inhalation and ingestion of dust and subsequent release of readily bioavailable elements sorbed on to dust, could lead to health issues such as lung or skin cancer, kidney dysfunction, hypertension, dermal lesions, peripheral neuropathy, and vascular disease. On 49 road dust and soil samples collected in the Metro Detroit area, we analyzed a suite of trace metals in <63 µm and size-separated road dust fractions to quantify the extent of metal enrichment and contamination status. We evaluated Enrichment Factor (EF), Pollution Index (PI), Geoaccumulation Index (GI), and Pollution Load Index (PLI). The average Chromium (Cr) concentration of 198 ppm is the highest reported for any global city in literature. The EF for Barium (Ba) was found ≥9 in all samples, and for the rest of other elements was >1.5. The PI values for Cr, Ba, Zinc (Zn), Lead (Pb), and Selenium (Se) indicate elevated levels and for Ba, Cr, and Zn up to a moderate level. PLI values in >50% of road dusts were ≥3, indicating many sites are ‘heavily polluted’. The PLI value in Detroit road dust is higher than those reported for many global cities, including Shanghai. Observed strong correlations between Cr-Zn and Cadmium (Cd)-Silver (Ag) likely indicate a common metal source. Cluster analysis of data for Cd, Arsenic (As), Pb, and Zn appears to be distinct between different proximally related clusters, while Nickel (Ni) and Ba are potentially more distinct between property type clusters. In general, metal concentrations of industrial samples are more commonly distinct with over half of metals (≥6 of 11) differing from residential and/or soil samples. Three generalized “groups” were identified from the combination of hierarchical cluster and PCA analyses followed by varimax rotation: Group 1 characterized by Cr, Cd, Ni, Ag, Zn, and Copper (Cu); Group 2 characterized by Pb, As, Mercury (Hg), and minor Ba; and Group 3 characterized by Se. This is the first study to report all four metrics of metal pollution along with rigorous statistical analysis.